Notes on the Text – Perception of the Text, (Non)Violation of Expectation, Recipient vs Author - Ondřej Krátky (ESPES, 2020)
The following paper is based on a broad understanding of communication (or the author-text-recipient relation) that considers as text basically anything that has been created within the framework of a cultural interaction by an author and that is perceived by a recipient. The first part of the paper introduces, explains and follows mostly cases in which the author’s violations of the recipient’s expectations have a communication value, i.e. provoke, in the recipient, a communication effect that matches the author’s intentions. In such cases, this effect results as a consequence of an (author-controlled) violation of the communication „cooperative“ principles. This, at the recipient’s end, translates into an event of expectancy violation. Each of such violations provokes an arousal in the recipient, which further motivates him/her to search for its cause. Finding this cause, and being “confronted” with the related violation pertaining to it with the norm equals, for the recipient, getting to the meaning of the text, or identifying its communication value etc. As part of the conclusion, a commented scheme is presented which offers a spectrum of possible communication outcomes “positioned” between the predictability of each textual element and the (author’s latent) stochasticity of choice. The effort to illustrate all the explained facts results, in the paper, in a rich set of examples stemming from miscellaneous spheres of human activity – from “high (artistic) styles” to rather day-to-day activities, to pop-culture. The objective is to show that the described principles, if not valid in general, permeate at least all forms of interaction.